2016
DOI: 10.1021/acs.analchem.6b01261
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase Tagged Antibodies on Gold Nanoparticles/TiO2 Nanotubes Electrode: A Plasmonic Strategy for Label-Free and Amplified Photoelectrochemical Immunoassay

Abstract: This work reports a plasmonic strategy capable of label-free yet amplified photoelectrochemical (PEC) immunoassay for the sensitive and specific detection of model protein p53, an important transcription factor that regulates the cell cycle and functions as a tumor suppressor. Specifically, on the basis of Au nanoparticles (NPs) deposited on hierarchically ordered TiO2 nanotubes (NTs), a protein G molecular membrane was used for immobilization of alkaline phosphatase (ALP) conjugated anti-p53 (ALP-a-p53). Due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…10a). 101,102 It is also reported that PICS-based photocurrents from antibody-modified Au NPs on TiO 2 are increased by selective binding of the antibodies to the corresponding antigens. 103 …”
Section: Applications Of Picsmentioning
confidence: 99%
“…10a). 101,102 It is also reported that PICS-based photocurrents from antibody-modified Au NPs on TiO 2 are increased by selective binding of the antibodies to the corresponding antigens. 103 …”
Section: Applications Of Picsmentioning
confidence: 99%
“…The photoelectrochemical( PEC) strategy as ap otential assay methodh as received increasing research interest in analytical fields due to its intrinsic advantages over traditional assay, such as highers ensitivity,e asier operation procedures, and lower background signal. [1][2][3][4][5] Poly{4,8-bis [5-(2-ethylhexyl)thiophen-2-yl]benzo[1,2-b:4,5-b']d ithiophene-2,6-diyl-alt-3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno [3,4-b]thiophene-4,6-diyl} (PTB7-Th) as ad onor-acceptor (D-A)-type photoelectricm aterial has been widely applied in PEC biosensors, owing to its merits of good film-forming properties, excellent chemical stability,a nd easy operation procedure;t hus it can produce a stable PEC signal withouta ny addition of electron donors or acceptors. [6][7][8] Considering that the photogenerated signal of PTB7-Th was limited by its restricted photoelectric conversion efficiency (PCE), much effort has been madet oi mprove the PCE of PTB7-Th.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of PEC biosensors that have the analyte functionalized onto the photoelectrode, the analyte of choice is selectively bound to the photoelectrode. Common methods for binding of analytes include analyte binding to DNA strands [127][128][129][130][131] , aptamer-analyte reactions [132][133][134] , and antibody-antigen reactions [135][136][137] . The bound analyte itself may alter the PEC performance of the photoelectrode [132-135, 136, 138] or a secondary probe may be bound selectively to the photoelectrode at sites where the analyte is already bound [127-131, 137, 139] to modulate the PEC performance of the photoelectrode.…”
Section: Photoelectrochemical (Pec) Biosensorsmentioning
confidence: 99%
“…A commonly employed technique for modulating the PEC performance of photoelectrodes in PEC biosensors is increased charge transfer resistance at the photoelectrode surface due to the presence of bound analyte and bound secondary probes. [132][133][134][135][136][140][141][142][143] The presence of biological analytes such as proteins or large probes conjugated to the analyte can impede the diffusion of reactants through steric hinderance to the photoelectrode surface. In addition, the presence of the bound analyte (and bound probes) blocks electrochemically active sites on the photoelectrode surface.…”
Section: Photoelectrochemical (Pec) Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation